2002
DOI: 10.3168/jds.s0022-0302(02)74284-7
|View full text |Cite
|
Sign up to set email alerts
|

Peptides From the N-terminal End of Bovine Lactoferrin Induce Apoptosis in Human Leukemic (HL-60) Cells

Abstract: To determine the effects of the multifunctional iron-binding glycoprotein, lactoferrin (LF) and related compounds on the growth of leukemic cells, human myeloid leukemic cells (HL-60) were exposed to bovine lactoferrin (bLF) and proteolytic hydrolysates of bLF. Pepsin hydrolysates of bLF showed a greater growth suppressive effect than tryptic hydrolysates or mature bLF. Four peptides with proliferation inhibition activity were purified from pepsin hydrolysates by ion-exchange chromatography, reverse-phase HPLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
68
0
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 24 publications
(25 reference statements)
2
68
0
4
Order By: Relevance
“…A lactoferricina, peptídio formado dos resíduos 17-41, resultante da ação da pepsina sobre a lactoferrina, apresenta além da atividade antimicrobiana 23 , ação apoptótica sobre células da leucemia humana 24 .…”
Section: Atividade Antimicrobiana E Antiviralunclassified
“…A lactoferricina, peptídio formado dos resíduos 17-41, resultante da ação da pepsina sobre a lactoferrina, apresenta além da atividade antimicrobiana 23 , ação apoptótica sobre células da leucemia humana 24 .…”
Section: Atividade Antimicrobiana E Antiviralunclassified
“…The antioxidant activity of milk protein hydrolysates has been interestingly described [24][25][26][27], and also individual peptide released after hydrolysis from a s -casein have been shown to possess free radical scavenging activities inhibiting enzymatic and nonenzymatic lipid peroxidation [28]. Moreover, a number of recent studies have shown that milk-derived peptides exert cytomodulatory activity playing a role in the regulation of cell growth, differentiation, and apoptosis [29][30][31]. A previous study on the CaCo2 cell line suggested that the complex peptide fraction of the buffalo milk waste whey (BWW), resulting from production of buffalo Mozzarella cheese had antioxidant and cytomodulatory properties [32].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that bovine Lactoferricin (LfcinB) has antimicrobial activity higher than the intact protein bovine Lactoferrin (LfB) (Bellamy et al 1992a, b;Bellamy et al 1994), and that it is the most active among the other Lfcins of human, murine and caprine origin (Vorland et al 1998). Moreover, not only is LfcinB active against gram-positive as well as gram-negative bacteria, fungi, and protozoa Gifford et al 2005), but it also shows antiviral and antitumor properties (Anderson et al 2003;Eliassen et al 2002;Roy et al 2002).…”
Section: Introductionmentioning
confidence: 96%